The effect of repeated stimulated granulocyte donations on hematopoietic indexes in donors: a 24‐year donor center experience. Issue 1 (16th November 2018) - Szymanski, James; Troendle, James; Leitman, Susan; Hong, Hong; Yau, Yu Ying; Cantilena, Cathy
Abstract : BACKGROUND: Short‐ and long‐term effects of mobilization regimens in hematopoietic stem cell and granulocyte donors have been well characterized. In this study, we examined the longitudinal hematopoietic changes related to repeat stimulated granulocyte donation. STUDY DESIGN AND METHODS: Complete blood counts for consecutive granulocyte donors between October 1994 and May 2017 were compared to unstimulated granulocyte donors. Plateletpheresis donors served as controls. The longitudinal change in precollection white blood cell (WBC) counts for these donor groups were modeled using a linear mixed‐effects model. The investigated variables were granulocyte, lymphocyte, and monocyte counts and the granulocyte collection yield. Contrasts were performed to explore the effect of donation number on precollection counts. RESULTS: For the granulocyte–colony‐stimulating factor plus dexamethasone (G‐CSF/Dex)–stimulated group, both the granulocyte and the lymphocyte counts decreased 6.51 × 10 9 /L (−23.1%, p < 0.001) and 0.21 × 10 9 /L (−20.4%, p < 0.001), respectively, between Donation 1 and Donation 20. This effect was still present at the 3‐ to 4‐year interval (b = −0.0008313, SE = 0.00029, p = 0.004). For the unstimulated donor group between Donation 1 and Donation 20, the lymphocyte count decreased by 0.62 × 10 9 /L (−51.5%, p < 0.001). This effect was only significant up to Year 2 (b = −0.0026, SE = 0.0010, p = 0.013). CONCLUSIONS: Past granulocyte donations were found to have a statistically strong negative effect on precollection granulocyte counts and lymphocyte counts and decreased granulocyte yield both in the G‐CSF/Dex–stimulated donors and the unstimulated donors. In this statistical model, for both these groups, the effect of past donations on granulocyte and WBC counts were still detectable 2 years later.